Multilevel correlates of domain-specific physical activity among rural adults - a cross-sectional study - Alan M. Beck; Natalicio H. Serrano; Audrey Toler; Ross C. Brownson (BMC, 2022)
Abstract Background Increasing physical activity (PA) in rural communities is a vital prevention tactic in multiple chronic diseases; however, little is known on the multilevel correlates of PA rural areas. A better understanding of domain-specific PA adds context for promoting PA in rural communities. The current study sought to determine factors associated with domain-specific and overall moderate-vigorous physical activity (MVPA) in rural communities. Methods Surveys were conducted across 14 rural mid-Western communities, with the final analytical sample including 1241 adults (ages 19-96, M = 57.0 [SD = 16.7], 67.8% female, 83.8% white). Generalized linear models with negative binomial distributions examined the relation between demographics, trail use, and perceptions of the neighborhood environment, with domain-specific and overall MVPA, measured via the Global Physical Activity Questionnaire. Results Rural residents reported an average of 617 total minutes of weekly MVPA (SD = 1141), with 58.5% meeting MVPA guidelines. Higher age, female gender, and higher educated individuals had lower levels of overall and occupational MVPA. Females, higher education, and perceived indoor recreational access were associated with lower levels of transportation-related MVPA, while trail use was associated with increased transportation MVPA. Higher age and female gender respondents had lower levels of recreational MVPA, while trail users and those who perceived favorable indoor recreational access had higher levels of recreational MVPA. Conclusions PA primarily occurred in the occupational domain among this sample of rural mid-Western adults. Findings highlight the need for multilevel interventions to address PA across multiple domains in rural communities, especially among females and older adults.